CITRA PEREMPUAN DALAM NOVEL DI ATAS SIANG DI BAWAH MALAM KARYA PUTU OKA SUKANTA: KAJIAN FEMINISME - Wilda, Supiya; Hudiyono, Yusak; Purwanti, Purwanti (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The purposes of this research were to find women's psychic and physical images, aims to describe the facts of the story, the psychological and physical images of women in female characters. This research uses a descriptive qualitative approach and is included in the type of literature. The source of the research data is the novel Above Siang Di Bawah Malam by Putu Oka Sukanta. The data collection techniques used were reading and note taking techniques. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results of this study indicate that the psychic images of the figures Josi, Lian, Ade, Gustini, Kiki, Lis, Lisa, Mimin, Ida, Romi, Elok, Rosi and Jasminah are almost similar, because of all the figures work as sex workers. From the point of view of their education is very minimal, therefore on average their thinking is limited as is the movement in their place of residence. In contrast to the figures of Dokter Niah and Field of Nunung who work like doctors and nurses, they are also figures who struggle with more advanced thinking. In the physical image, Josi, Lian, Ade, Gustini, Lis, Lisa, Mimin, Ida, Romi, Elok, Rosi and Jasminah are women who work as sex workers, they are depicted by dressing, dressing up in menor, creased, and neglected.